Comparison of parturient - controlled remifentanil with epidural bupivacain and sufentanil for labour analgesia: randomised controlled trial - Stourac, Petr; Suchomelova, Hana; Stodulkova, Marta; Huser, Martin; Krikava, Ivo; Janku, Petr; Haklova, Olga; Hakl, Lubomir; Stoudek, Roman; Gal, Roman; Sevcik, Pavel (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2014)
INTRODUCTION: Epidural analgesia (EA) has significant contraindications including coagulation disorders and parturient refusal. One alternative is intravenous self-administered analgesia using the ultra short-acting opioid remifentanil (rPCA). We compared the efficiency and safety of standard epidural analgesia with parturient-controlled intravenous analgesia using remifentanil as well as personal satisfaction. MATERIALS AND METHODS: We enrolled twelve ASA I classified women with singleton pregnancy who delivered vaginally in the period 3/2010-5/2010 and who received rPCA (n=12) in standard analgesic protocol: 20 µg boluses using PCA pump with a lockout interval of 3 min. The control group consisted of 12 pregnant women who received EA (n=12): 0.125% bupivacaine with sufentanil 0.5 µg/mL in top-up boluses every hour until delivery. Data were acquired from standard Acute Pain Service (APS) form and patient medical records (demographic, labour course parameters), Visual Analogue Scale (VAS), Bromage Scale (BS) and adverse effects of analgesia. RESULTS: There were no demographic or labour course parameter differences between groups (P>0.05). The differences in VAS decrease (P=0.056) and parturient satisfaction (P=0.24) during the whole analgesia administration were statistically insignificant. The main limitation of the study was small sample and enrolment of healthy singleton pregnant women only. CONCLUSION: Remifentanil use in obstetric analgesia is a viable alternative to EA, especially in cases of EA contraindications and parturient disapproval.
Keywords: Analgesia, Epidural; remifentanil; Obstetric Labor Complications; komplikace porodu; těhotenství; Pain; Analgesics, Opioid; opioidní analgetika; Prospective Studies; sufentanil; mladý dospělý; Adult; Bupivacaine; Pain Measurement; měření bolesti; pacientem kontrolovaná analgezie; Young Adult; bupivakain; ženské pohlaví; Piperidines; Sufentanil; Anesthetics, Local; prospektivní studie; Humans; Pregnancy; porod; Remifentanil; dospělí; epidurální analgezie; anestetika lokální; piperidiny; Analgesia, Patient-Controlled; bolest; Female; Parturition; lidé